2016
DOI: 10.1589/jpts.28.491
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of muscular activities in the abdomen and lower limbs while performing sit-up and leg-raise

Abstract: [Purpose] This study compared the muscle activities of sit-up and leg-raise. [Subjects and Methods] The subjects of this study were healthy students in their 20s. For electromyography of sit-ups and leg-raises in the supine position, 5 muscle groups of the abdomen were selected for the attachment of sensors: the upper and lower rectus abdominis, external oblique, rectus femoris, and the iliopsoas. SPSS 20.0 was used for the statistical analysis. One-way ANOVA with repeated measures of all factors was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
(10 reference statements)
1
7
0
Order By: Relevance
“…This is in line with the findings of Kim et al [5] who also did not observe differences in RA thickness between curl-up and leg raises. Results on EMG differences between these particular trunk exercises are conflicting as some studies [3,12,14] found that combined trunk and leg lifting exercises display greater EMG activation of RA than leg lift while others reported greater RA activation either during trunk lift [9] or during leg lift [13]. Comparisons with our findings is difficult as these studies [3,13,14] used EMG during dynamic movements as opposed to US thickness during isometric efforts implemented in this study.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…This is in line with the findings of Kim et al [5] who also did not observe differences in RA thickness between curl-up and leg raises. Results on EMG differences between these particular trunk exercises are conflicting as some studies [3,12,14] found that combined trunk and leg lifting exercises display greater EMG activation of RA than leg lift while others reported greater RA activation either during trunk lift [9] or during leg lift [13]. Comparisons with our findings is difficult as these studies [3,13,14] used EMG during dynamic movements as opposed to US thickness during isometric efforts implemented in this study.…”
Section: Discussionmentioning
confidence: 55%
“…Other studies set the upper and lower RA 3 cm vertically up and down from the umbilicus, respectively [5] while other investigators took measurements from the second portion [20] or the midpoint between portions [21] below and above the umbilical level. Third, in some studies exercises were performed at low intensity [21] or with active movement [9,14] which is different to maximum isometric contractions monitored in this study. Finally, another factor that could affect comparisons between studies is the angle of trunk and hip flexion at which the measurements were taken.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The exercise is similar to the curl-up or crunch, but the main difference is that the aim of the sit-up is to lift the trunk until the participant is upright in a semi-seated position. This exercise may vary depending on specific protocols (e.g., sit-ups on unstable surfaces) [16,25,58,60].…”
Section: Sit-upmentioning
confidence: 99%